Edukasi Digital Marketing Kepada Pelaku Usaha di Desa Sampe Cita Kecamatan Kutalimbaru Kabupaten Deli Serdang - Lubis, Hidayati Purnama; Virdyra Tasril; Riska Franita; Firdiya Amiyananda (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
The implementation of this community service aims to educate and increase the understanding of the people of Sampe Cita Glugur Rimbun Village, Kutalimbaru District, Deli Serdang Regency about one way to market a product produced.  This special target in community service seeks to socialize and educate that marketing strategies to introduce products produced by business actors have changed patterns along with the development of technology that continues to increase, including online using the internet network called digital marketing which is interpreted as digital marketing. This method of implementing community service is by making presentations, lectures and questions and answers to the participants.  The topics of the material presented include: what is digital marketing (understanding digital marketing), what facilities can be used as a place for digital marketing, what are the benefits of digital marketing. The results obtained from this community service show that the participants, namely business actors in Sampe Cita Glugur Rimbun Village, Kutalimbaru District, Deli Serdang Regency can know and understand the concept of digital marketing of a product produced by business actors, in an effort to introduce and market existing products easily, cheaply, quickly and efficiently.